2020
DOI: 10.1073/pnas.1919563117
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and bisphenol S disruptions of the mouse placenta and potential effects on the placenta–brain axis

Abstract: Placental trophoblast cells are potentially at risk from circulating endocrine-disrupting chemicals, such as bisphenol A (BPA). To understand how BPA and the reputedly more inert bisphenol S (BPS) affect the placenta, C57BL6J mouse dams were fed 200 μg/kg body weight BPA or BPS daily for 2 wk and then bred. They continued to receive these chemicals until embryonic day 12.5, whereupon placental samples were collected and compared with unexposed controls. BPA and BPS altered the expression of an identical set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 90 publications
0
72
0
1
Order By: Relevance
“…Additionally, during organogenesis and tissue repair different cell types with different receptors interact to form organs, increasing the complexity of interactions and thus the likelihood of non-monotonic dose-response curves [231]. But, perhaps more importantly, we applied a rigorous mixOmics approach [21], as done in previous BPA studies performed in the Rosenfeld Laboratory [22][23][24], to ascertain whether the low dose of BPA simultaneously affected several endpoints in different laboratories. As such, if low-dose effects in the same animals are identified across multiple systems, it seems unlikely that these findings are not important.…”
Section: Integrated Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, during organogenesis and tissue repair different cell types with different receptors interact to form organs, increasing the complexity of interactions and thus the likelihood of non-monotonic dose-response curves [231]. But, perhaps more importantly, we applied a rigorous mixOmics approach [21], as done in previous BPA studies performed in the Rosenfeld Laboratory [22][23][24], to ascertain whether the low dose of BPA simultaneously affected several endpoints in different laboratories. As such, if low-dose effects in the same animals are identified across multiple systems, it seems unlikely that these findings are not important.…”
Section: Integrated Discussionmentioning
confidence: 99%
“…To achieve these lofty goals, we used the mixOmics R package [21], as we have done in previous BPA studies performed in the Rosenfeld Laboratory [22][23][24]. In this case, we used the program to correlate data obtained by independent CLARITY-BPA investigators.…”
Section: Integrative Correlation Analysis For Independent Clarity-bpamentioning
confidence: 99%
See 1 more Smart Citation
“…To examine for potential associations between those genes that were identified by false discovery rate (FDR) to be differentially expressed and phenotypic changes, Pearson correlations were performed, as we have done previously (Manshack et al, 2017;Mao et al, 2020). This was done two ways: 1) values were calculated across all mice and 2) only based on female results, as these were the most pronounced.…”
Section: Statisticsmentioning
confidence: 99%
“…One study, however, suggests that the placenta relies on transport of maternal 5‐HT (Kliman et al, 2018). In our recently published studies, we found that exposure to endocrine‐disrupting chemicals (EDC), bisphenol A (BPA) and bisphenol S (BPS) lower the total concentrations of 5‐HT in the placenta (Mao et al, 2020). Additionally, we localized 5‐HT to trophoblast giant cells, which are in contact with the underlying uterine tissue, but the number of giant cells staining immunopositive for 5‐HT was reduced with BPA or BPS exposure (Mao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%